Funcionarios Dirección Distribución de Materiales : Minor Corella, Guillermo Mora, Alejandro Rojas Sanabria, Carlos Elizondo, Hernán Mora, Wallace Davis. - Universidad Estatal a Distancia (San José, Costa Rica : UNED, 2024)
Grupo mediano de personas
Colección Fototeca UNED
Keywords: Corella, Minor; Mora, Guillermo; Rojas Sanabria, Alejandro; Elizondo, Carlos; Mora, Hernán; Davis, Wallace; FOTOGRAFÍAS; UNIVERSIDAD ESTATAL A DISTANCIA -- COSTA RICA; FOTOTECA